Research of the working conditions noise factor in the foundry production - A. M. Lazarenkov; M. A. Sadokha (Литьë и металлургия)
The research results of the noise effect on workers in the foundry are presented. The main sources of noise are shown. An assessment on the noise factor of various professions of the foundry was made. Recommendations on the assessment and measuring of noise in the design of new and reconstruction of existing foundries are given.